Manajemen Risiko Kesehatan, Keselamatan, Kerja dan Lingkungan (K3L) pada Proyek Pembangunan Embung Tukad Unda Provinsi Bali - Suryawan, M. Alit; Sutarja, I Nyoman; Pariartha, I Putu Gustave Suryantara (Universitas Batanghari Jambi, 2025)
The construction work of the Tukad Unda Reservoir is located in a former sand quarry area characterized by water-filled pits and unstable coral aggregates. This area also serves as a lahar flow path during eruptions of Mount Agung, which remains active. This condition was identified through geological and geotechnical sampling tests. The aim of this study is to analyze the Occupational Health, Safety, and Environment (HSE) risks that can be identified in this project. Data were collected through interviews, brainstorming sessions, and field observations. Risk coefficients were scored based on risk acceptability. The assessment focused on dominant risks that require management actions, specifically those categorized as “high” and “very high” risk levels. The final identification results revealed a total of 75 risks based on the type of work, consisting of 28 risks (37%) in sub-structural work, 41 (55%) in structural activities, and 6 (8%) in architectural activities. Based on the sources of risk, 26 risks (35%) originated from equipment, 27 (36%) from materials, and 22 (29%) from environmental factors. In terms of impact targets, 64 risks (85%) affect humans, 10 (13%) affect both humans and the environment, and 1 (1%) affects the environment alone. Based on the analysis using the AS/NZS 4360:2004 standard, 17 risks (23%) were classified as low risk, 39 (52%) as medium risk, and 19 (25%) as high risk. Risk ownership was predominantly allocated to the contractor's HSE supervisors (56%), followed by site managers (35%) and technical staff (9%). It is recommended that competent and authorized personnel at the project site conduct safety briefings before commencing any work activities to minimize the potential for unwanted incidents. Workers are also advised to pay more attention to occupational health and safety by wearing appropriate personal protective equipment (PPE) and complying with all established regulations and standard operating procedures (SOPs).